A comparison of match demands using ball-in-play vs. whole match data in elite male youth soccer players. Issue 2 (2nd April 2020) - Wass, Josh; Mernagh, Dylan; Pollard, Ben; Stewart, Perry; Fox, Wesley; Parmar, Nimai; Jones, Ben; Kilduff, Liam; Turner, Anthony N.
ABSTRACT: Instruction : Effective playing time in soccer is typically < 60 min per game and while players may reposition themselves when the ball is out of play, it is likely the physical demand decreases during this period. Therefore, if this period is included in data when quantifying match demands, it may under-report the physical requirements of soccer players. This study investigated an alternative method for quantifying external workload called ball in play (BiP), which analyses the data excluding stoppages, and thus potentially offers a more insightful analysis of match demands.Methods : Whole match demands as typically recorded via GPS, were compared to those based on BiP, and maximum BiP, with the latter representing worst case scenario phases of play. The 25-elite male youth soccer players (age: 17.9 ± 0.6 years; height: 174.8 ± 6.2 cm; body mass: 66.3 ± 8.1 kg) who participated in this study were also categorised in to positional groups (defender, midfielder, and forward) to assess differences in positional demands.Results : While no differences were noted based on position, whole match metrics were significantly lower than mean and maximum BiP metrics (p < 0.05). There was also a significant difference for maximum BiP outputs across different in-play durations, when comparing 30-60 seconds, 60–90 seconds, and > 90 seconds.Conclusion : This data allows practitioners to gain a deeper understanding of the physical demands imposed on players and plan sessions using targets that better represent match demands.